Forest cover monitoring of Bara district (Nepal) using remote sensing and geographic information systems - Kandel, CM; Caetano, M; Cabral, P (Banko Janakari, 2010)
This study uses Landsat TM of 1989 and ETM+ of 1999 and 2005 imagery to evaluate forest cover dynamics during 1989-2005 in the Bara district of Nepal. The aim of the study was to analyse the extent and trend of forest cover dynamics, spatial pattern of forest and their driving forces. Forest cover change analysis was performed using objectoriented classification approach applying a standard nearest neighbour algorithm to classify the image in recognition. The overall classification accuracies were 85.71% and 88.23% for the year 1999 and 2005, respectively. Land cover maps were produced with seven land cover categories and were further reclassified as forest and non-forest areas to analyse the forest cover dynamics. Post-classification and time series analysis were carried out to detect the changes. Spatial metrics were computed for detecting the spatial pattern of forest. The classifications suggested that the amount of forest land had decreased by 11.56% during 1989-2005. Spatial metrics revealed that forest area has been fragmented and deforested with an annual rate of 0.72%. The overall result demonstrates that forest area has experienced a significant shrinkage and mostly transferred into agricultural and bare land. Expected change for the year 2021 was projected using Markov Chain Analysis (MCA). The MCA result showed that forest area would decrease by 8.5% in the period of 2005-2021. Key words: Forest cover dynamics; geographical information systems; landsat; remote sensing; spatial metrics DOI: 10.3126/banko.v20i1.3506 Banko Janakari, Vol. 20, No. 1 pp.30-36